Analysis of the adoption process of instant noodle giving behavior to toddlers: A phenomenological study of learn, feel, and do in mothers - Nuraeni (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Instant noodles given by mother to toddler can be bad for the toddler's health, especially if presented without additional material containing protein, minerals or vitamins. The purpose of this study is to determine the stage of learning, feel and experience by informants in adopting the behavior of giving instant noodles to toddlers. Method: Researchers use qualitative approach methods with phenomenology design. The research data was collected through interviews and observation of 23 informants consisting of mother of toddler, family of toddler and Nutritional Implementer of health center/Pusat Kesehatan Masyarakat (Puskesmas) Turikale. The data is then processed using content analysis. Findings: Sources of informant information are personal experiences, friends, television and internet. Informants know the side effects of instant noodles such as allergies, digestive disorders, and addictions. Informants also looked at instant noodles as a practical food, affordable, easy to find, and to increase the appetite of toddlers. Conclusion: Based on the result of the research, it can be concluded that at the stage of learning is found the reason for giving instant noodles due to the child's desire factor and belief to the excess of instant noodles, while at the feel of informant stage confident of the danger of instant noodle but not bigger than the child's desire factor, to stage do with the pattern of adoption trial-do is to try some practices such as giving instant noodles that are not berkuah with additional ingredients that informants provide eggs and green mustard greens. Novelty/Originality of this article: The novelty of this study lies in the use of the learn, feel, and do approach to analyze the process of adopting instant noodle-giving behavior in toddlers, focusing on the mother's internal conflict and the trial-do adoption pattern. This study is also unique because it uses a phenomenological method to explore various factors influencing mothers' decisions, including social, economic, and psychological aspects, and identifies diverse sources of information shaping their knowledge and perceptions.